Hydrothermal acid treatment for sugar extraction from Golenkinia sp. (August 2015) - Choi, Sun-A; Choi, Won-Il; Lee, Jin-Suk; Kim, Seung Wook; Lee, Gye-An; Yun, Jihyun; Park, Ji-Yeon
Graphical abstract: Highlights: Hydrothermal acid treatment for sugar extraction from wet microalgae. The maximal sugar extraction yield at 2.0% sulfuric acid concentration. An improvement of sugar yield with enzymatic hydrolysis combination. Abstract: In this study, hydrothermal acid treatment for efficient recovery of sugar from Golenkinia sp. was investigated. The initial glucose and XMG (xylose, mannose, and galactose) contents of a prepared Golenkinia sp. solution (40 g/L) were 15.05 and 5.24 g/L, respectively. The microalgal cell walls were hydrolyzed, for sugar recovery, by enzymatic saccharification and/or hydrothermal acid treatment. Among the various hydrothermal acid treatment conditions, the most optimal were the 2.0% H2 SO4 concentration at 150 °C for 15 min, under which the glucose- and XMG-extraction yields were 71.7% and 64.9%, respectively. By pH 4.8, 50 °C enzymatic hydrolysis after optimal hydrothermal acid treatment, the glucose- and XMG-extraction yields were additionally increased by 8.3% and 0.8%, respectively. After hydrothermal acid treatment, the combination with the enzymatic hydrolysis process improved the total sugar yield of Golenkinia sp. to 75.4%.